LITERATURE REVIEW: HUBUNGAN STATIC BALANCETERHADAP RISIKO TERJADINYA CEDERA PADA PEMAINSEPAK BOLA - FARAH GHANIYYAH (2020)
Objective: Static balance is the balance needed in various aspects of postural control, especially in football games. There is currently little known relationship between static balance and the risk of injury to a soccer player. This research was conducted for the purpose of studying literature, articles, and journals with the results of research on the relationship of static balance to the risk of injury to soccer players. Method: The source of data in this research is to use several databases such as Google Scholar, PubMed, Science Direct by using some of the keywords needed. From the literature search results there are 3 articles and journals that meet the source inclusion criteria. Source of assessment methodology for 3 articles with Scimago Journal & Country Rank (SJR) and journal analysis using the appropriateness of research methods, topics used, parameters, and the results of each article. Results: After reviewing the literature with 3 articles, it shows that static balance can reduce the risk of injury to soccer players. Conclusion: Static balance can reduce the risk of injury to soccer players significantly.